No-Code Mobile Chatbot App Development Using MIT App Inventor - Abdl Aziz, Noraisyah; Rashidah Mokhtar; Nooradilla Abu Hasan; Muhammad Nur Iman Muslim Reymi (Applied Information Technology And Computer Science, 2025)
Nowadays, Artificial Intelligence (AI) is making a significant impact on the advanced technology landscape in education, including personalized learning, intelligent tutoring systems, automated grading, predictive analytics, and chatbots. This paper presents the design and development of a chatbot mobile app that eases the search for information using text-based and voice-enabled information retrieval. The development process, adapted from the Mobile application development lifecycle, encompasses key phases such as identification, design, development, prototyping, testing, deployment, and maintenance. MIT App Inventor is used as a development tool, offering a visual environment with minimal coding experience required. The app demonstrates simplified AI integration in mobile solutions. This study offers insights gleaned from overcoming challenges in integrating diverse tools and AI functionalities, aiming to inspire young developers to make an effort to develop practical AI applications.